Statistical theory and methods for evolutionary genomics - Gu, Xun. (Oxford : Oxford University Press, 2011)
Summarising the statistical framework of evolutionary genomics this text illustrates how statistical modelling and testing can enhance our understanding of functional genomic evolution.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Genomics -- Statistical methods